The dissertation examination: identifying critical factors in the success of Indigenous Australian doctoral students. Issue 1 (2nd January 2017) - Harrison, Neil; Trudgett, Michelle; Page, Susan
Abstract : Indigenous Australians represent 2.2% of the working age population, yet account for only 1.4% of all university enrolments. In relation to higher degree research students, Indigenous Australians account for 1.1% of enrolments, but only 0.8% of all higher degree research completions. This paper reports on findings that emerged from an Australian Research Council-funded study which aimed to establish a model of best practice for the supervision of Indigenous doctoral students. The project identified the dissertation examination as one of the critical factors underpinning the success of doctoral candidates. Whilst research into the examination process for doctoral students is limited, the research that specifically explores the examination of dissertations submitted by Indigenous students is entirely inadequate. Our research identified key epistemological concerns that impact approaches to the examination process, to demonstrate how the dominance of Western methods of research impact the examination process for Indigenous doctoral students. This paper explores the experiences of 50 successful Indigenous Australian doctors with a specific focus on their examiner preference and disciplinary requirements. It highlights the limitations that some Indigenous students and their supervisors experience in finding an appropriate examiner.